Thermogravimetric Study of Gadolinium Chlorotungstate in Air Between 25 and 1500°C. - Ngassapa, F N; Venskovskii, N U (Tanzania Journal of Science, 2021)
Using DTA, X-ray powder diffraction, chemical and optical methods, the thermostability of Gd3WO6Cl3 was investigated. The compound was relatively stable on heating in air up to 710oC. Above this temperature it exhibited two decomposition temperature ranges (710-900oC and 900-1130oC). The final product consisted of a mixture of gadolinium tungstate of different composition. This suggests the decomposition scheme of polyphase products